Statistics : a tool for social research - Healey, Joseph F. 1945- (Wadsworth Cengage Learning, 2012)
Provides an introduction to the fundamental concepts of statistics and their practical application to a variety of contemporary social issues. This title covers hand calculations and the use of computers, providing a grounding in both traditional formulas and the SPSS statistical software package